Activation of Coke Fines Using CO2 and Steam: Optimization and Characterization of Carbon Sorbents - Aigul T. Ordabaeva; Zainulla M. Muldakhmetov; Mazhit G. Meiramov; Sergey V. Kim (Molecules)
In this study, the characteristics of coal sorbents obtained by the activation of coke fines in an atmosphere of a mixture of gases CO2 and H2O were studied. The experiment was conducted at various temperatures (700–900 °C), activation time (60–180 min), and constant CO2 supply rate (0.5 L/min). The main parameters such as tinder, ash content, bulk density, sorption capacity, total pore volume, and specific surface area were analyzed to assess the efficiency of the process. The results showed that samples of sorbents obtained at a temperature of 800 °C and an activation time of 120 min have the highest sorption capacity for iodine (up to 64.77%). The specific surface area of the obtained carbon sorbents was ~432.6 m2/g. It was found that an increase in temperature to 900 °C leads to a decrease in sorption characteristics, which may be due to partial destruction of the porous structure of the material. It was also found that the duration of activation contributes to an increase in burn-off and ash content, which had an effect on sorption properties. Based on the data obtained, optimal conditions for the production of carbon sorbents have been established and a process model has been developed.